PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. HADJI KALLA - Nurmiati Nurmiati (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2014)
This study aims to determine the effect of motivation and the work environment either partially or simultaneously on the performance of employees at PT. Hadji Kalla. The population in this study were all employees at PT. Hadji Kalla as many as 120 people, but taken as a sample of only 50 people using nonprobability sampling, convenience sampling technique. Analysis of the data used is multiple regression analysis. The results showed that motivation and work environment variables either partially or simultaneously affect the performance of employees at PT. Hadji Kalla.